Effectiveness of Da'wah Programmes: A Case Study of Da'wah Programmes on TV3 - Mohamad Isa Bin Amat (Universiti Sains Islam Malaysia, 2009)
Mass media is perceived as a most influential medium to convey da'wah message to the people. Media's attraction especially television has the superior power to develop and establishing mind setting, culture, and value system of community. Apparently, we don't want our generation involved with violence, wrongdoing which is totally against our religion. We want our next generation is developing as to potential leaders in the future, which enriched by positive attitude and good manner. Therefore, this study is essential to recognize the audience's perception towards da'wah programmes. At the same time it aims to identify on how much television gives the positive impact to better society. In our efforts to get the higher recognition in society, educating the youth generation is necessary for long-term benefits because the youth is our priceless assets of country. Regarding this awareness, the field research about da'wah programmes in electronic media had been constricted. This research had been done in district of Ampang Jaya which 89 respondents were interviewed to clear views concerning public's perception and the effectiveness level of da'wah programmes. Hopefully, this study would be able to expose and address resolution and sharing the ideas in order to increasing the community's understanding and awareness towards da'wah programmes.